Dolgaya Spit: Tourism on the Azov Seacoast - VOLKOVA, Tatiana Aleksandrovna (Journal of Environmental Management and Tourism, 2019)
The Krasnodar region is one of Russia’s four leaders in terms of tourism development. The number of tourists who visit the Krasnodar region has been rising year after year. Specially protected natural areas, which attract a lot of tourists, come under pressure. Nowadays, natural monuments turned into travel destinations, as a rule, of short-term trips (the so-called weekend journeys). The Dolgaya Spit area is an example of extensive use of natural monuments. It can be expected that tourist flow might exceed the current level, maybe by several times, on the back of rising popularity, the development of transport infrastructure and improved beach quality. To date, the failure to resolve the current problems for a long time has led to unfavorable consequences, with the natural monument degrading rapidly amid growing recreational pressure. The situation is quite complicated. On the one hand, the area’s economic prospects as a resort are unquestionable, although, on the other hand, the Dolgaya Spit needs protection because it is now under the influence of constantly rising anthropogenic factors.